Cybersecurity and Executive Power - David W. Opderbeck (Washington University Law Review, 2012)
This Article analyzes the constitutional authority of the President to shut down or limit public access to the Internet in a time of national emergency. The threats posed by cybercrime, cyberwarfare, and cyberterrorism are significant. It is imperative that national governments and international policymakers develop defenses and contingency plans for such attacks. At the same time, the threats to civil liberties posed by current legislative cybersecurity proposals are equally real. Executive power to disrupt Internet access in the name of security can become as potent a weapon against democracy as a hacker’s attempt to take down the power grid. This Article examines current cybersecurity proposals in Congress and explains why they are in many ways misguided. It then examines the constitutional law of presidential power against the backdrop of recent efforts by Congress and the Executive to regulate cyberspace. The Article concludes with a proposed cybersecurity policy matrix, which could help courts and policymakers manage the difficult constitutional and policy tensions raised by the problem of cybersecurity.
Keywords: Cyberterrorism; Data security; Executive power; United States